Development of improvised testing procedures for the structural properties of wall sheathing panels - Ventura, John Lenard D.J.; Germar, Fernando J.; Aquino, Diocel Harold M. (Quezon City College of Engineering, University of the Philippines Diliman, 2015)
Temporary Shelter Systems are essential structmes for the transition period from disaster to the recovery of victims of natural calamities and is a decisive factor in their return to normal life. As such, the planning and design of such structures should be well conducted to satisfy the needs of its beneficiaries. To ensure safety, its structural integrity should be evaluated such that it is able to withstand the forces and actions over its lifetime. Through experiments and testing, the strength and stiffness parameters of such temporary shelters is to be evaluated through one of its components which are structural wall sheathing panels. This study aims to develop improvised testing procedures for structural sheathing panels. A review of ASTM standard practices was done to determine the procedures for testing of these panels, considering the available equipment which is the VTM. Contraptions or attachments were designed and fabricated to carry out such test procedures on plywood for calibration. Actual tests are done, which showed that the setups are precise. Their precision is measured by percent differences of values, standard deviation and standard deviation of the mean, which amount to less than 50%. However accuracy is still in question as no suitable reference values are found. It was also concluded that wall performance on cyclic loading is critical with 30% decrease in strength and 13% decrease in stiffness. In addition, sheathing-to-frame connections control wall behavior against cyclic loading. Further tests by increasing samples or using other specimens (e.g. plastic) are recommended.
Thesis (B.S. Civil Engineering)--University of the Philippines Diliman
Keywords: Sheathing (Building materials) -- Testing; Emergency housing